THE IMPLEMENTATION OF PROJECT BASED LEARNING IN INTRODUCTION TO LITERATURE SUBJECT TO THE STUDENTS AT UNP KEDIRI - Nurhajati, Diani; Billy, Putri Diyah Rahayu (JURNAL KOULUTUS, 2023)
Introduction to Literature is a subject which objectives are that the students are able to appreciate a literary work and have soft skills. The lecturer chose Project Based Learning in which the students were assigned to perform drama for the final project. Therefore, this study aims to describe the stages of Project Based Learning and to describe the advantages and disadvantages of the learning activities. This research used a case study with a qualitative research approach. There were some techniques to collect the data, namely observation, interview, and documentation. The subjects of the research were the lecturer and three students as the representatives. In implementing Project Based Learning, the lecturer followed the following steps: 1) Start with an Essential Question; 2) Design Projects; 3) Create a Schedule; 4) Monitoring the Students and Progress of the Project; 5) Assess the Outcome; 6) Evaluate the Experience. The advantages of the learning activities are that the students learn how to collaborate with their peers, feel free to create the performance, and practice to communicate their ideas with their peers. The disadvantages the lecturer should design the learning activities carefully in order to reach the learning objectives.